Navigating Resource Tensions During Diversification in Ecosystems: Strategic Leadership Across Organizational Levels - Alao, Ayomide Peter; Khanagha, Saeed; Berends, Hans (Journal of Management Studies, 2026)
Abstract Ecosystem diversification extends joint value creation by developing new interdependencies between ecosystem actors while redeploying partners and their resources. Such diversification simultaneously generates tensions over ecosystem resources not controlled by the focal firm. This study examines how strategic leaders across organizational levels navigate these resource tensions. Based on a longitudinal case study of PetCo's diversification within the pet care ecosystem, we identify two types of ecosystem resource tensions – commensalistic and rivalrous – and show how each activates distinct patterns of leadership actions and outcomes. Commensalistic tensions prompt middle managers to lead peer‐level interactions that secure permissive partitioning of overlapping resources, granting multiple initiatives access to ecosystem resources. Rivalrous tensions, by contrast, require coordination across hierarchical levels, with senior managers intervening to enforce restrictive resource partitioning that limits or withdraws an initiative's access to resources, or, when senior and middle managers collaborate, to achieve permissive partitioning that sustains synergy across initiatives. We discuss implications for research on strategic ecosystem leadership and diversification.